Incidental findings on MRI for the evaluation of endometriosis: prevalence and clinical significance - Harth, Sebastian; Roller, Fritz Christian; Brose, Alexander; Kaya, Hasan Emin; Zeppernick, Felix; Meinhold-Heerlein, Ivo; Krombach, Gabriele Anja (Frontiers in Medicine, 2024)
Objectives: This study aimed to analyze the prevalence and clinical significance of incidental findings on MRI for endometriosis. Differences between patients with and without evidence of deep infiltrating endometriosis on MRI were to be examined.This was a retrospective, descriptive cross-sectional single-center study. All patients who received a pelvic MRI for endometriosis between April 2021 and February 2023 were included. The presence and frequency of incidental findings were noted after review of all MR images and radiology reports. The potential clinical significance of the findings was analyzed. Differences in the frequency of incidental findings between patients with and without evidence of deep infiltrating endometriosis on MRI were evaluated, utilizing the Chi-square test, Fisher's exact test and Mann-Whitney U test.Results: 303 consecutive patients (mean age, 33.4 years ± 8.3) were evaluated. Incidental findings were noted in 299/303 (98.7%) patients. Most frequently, ossification of the hip acetabular rim and degenerative changes of the lumbar spine were noted. In 25/303 (8.3%) patients, incidental findings had high clinical significance. For specific incidental findings, significantly higher prevalences were found in patients with than in patients without evidence of deep infiltrating endometriosis on MRI (hip acetabular rim ossification, p = 0.041; annulus fibrosus fissures, p = 0.006; gallstones, p = 0.042).Conclusions: Incidental findings are very common on pelvic MRI for endometriosis. The detection of incidental findings can lead to the diagnosis of relevant diseases and thus enable early treatment. On the other hand, many incidental findings have no, only minor, or uncertain consequences.